2018
DOI: 10.1002/ange.201808930
|View full text |Cite
|
Sign up to set email alerts
|

Amino‐Assisted Anchoring of CsPbBr3 Perovskite Quantum Dots on Porous g‐C3N4 for Enhanced Photocatalytic CO2 Reduction

Abstract: Halide perovskite quantum dots (QDs) have great potential in photocatalytic applications if their low charge transportation efficiency and chemical instability can be overcome. To circumvent these obstacles, we anchored CsPbBr3 QDs (CPB) on NHx‐rich porous g‐C3N4 nanosheets (PCN) to construct the composite photocatalysts via N−Br chemical bonding. The 20 CPB‐PCN (20 wt % of QDs) photocatalyst exhibits good stability and an outstanding yield of 149 μmol h−1 g−1 in acetonitrile/water for photocatalytic reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(96 citation statements)
references
References 51 publications
1
95
0
Order By: Relevance
“…Thus, continuous photocatalytic H 2 evolution from HBr splitting occurs. skite to the RGO is verified, suppressing the charge recombination and leading to the improvement of the H2 production [32,83,84]. The Cs2AgBiBr6/2.5% RGO sample exhibited the highest photocurrent as the lowest charge-transfer resistance than other samples, corresponding to the best photocatalytic H2 evolution activity [32].…”
Section: D Bi-based and Sb-based Mhpsdouble Mhpsmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, continuous photocatalytic H 2 evolution from HBr splitting occurs. skite to the RGO is verified, suppressing the charge recombination and leading to the improvement of the H2 production [32,83,84]. The Cs2AgBiBr6/2.5% RGO sample exhibited the highest photocurrent as the lowest charge-transfer resistance than other samples, corresponding to the best photocatalytic H2 evolution activity [32].…”
Section: D Bi-based and Sb-based Mhpsdouble Mhpsmentioning
confidence: 86%
“…In order to clarify the great improvement on H 2 evolution attributable to the preparation of perovskite/RGO composites, PL analyses and photoelectrochemical measurements on a working electrode obtained by the deposition of catalysts on FTO glass located in a workstation containing Ag/AgCl 3M as reference electrode and Pt mesh as counter electrode in an electrolyte solution of dichloromethane containing 0.1 M TBAPF6 were performed. Results allowed to conclude that for Cs 2 AgBiBr 6 /xRGO samples, a rapid transfer of photogenerated electron from the perovskite to the RGO is verified, suppressing the charge recombination and leading to the improvement of the H 2 production [32,83,84]. The Cs 2 AgBiBr 6 /2.5% RGO sample exhibited the highest photocurrent as the lowest charge-transfer resistance than other samples, corresponding to the best photocatalytic H 2 evolution activity [32].…”
Section: D Bi-based and Sb-based Mhpsdouble Mhpsmentioning
confidence: 87%
“…It should be noted that no H 2 was detected during the photocatalytic process, which could be ascribed to the absence of cocatalyst and the relatively high overpotential . In another work, Ou et al anchored CsPbBr 3 QDs on the surface of porous g‐C 3 N 4 through the N–Br interaction between the abundant NH x sites of porous g‐C 3 N 4 and the CsPbBr 3 QDs. The unique N–Br bonding state between the g‐C 3 N 4 and CsPbBr 3 QDs would result in the enhanced charge separation and a prolonged lifetime of the charge carriers.…”
Section: Photoelectrochemical Applications Of Ihpqdsmentioning
confidence: 99%
“…5) The solution also plays an important role in photocatalytic activity. For example, the photocatalytic CO 2 reduction activity of IHPQDs performed in acetonitrile was much higher than that in ethyl acetate/water, because acetonitrile has higher CO 2 solubility …”
Section: Photoelectrochemical Applications Of Ihpqdsmentioning
confidence: 99%
“…At present,t he most commonly used organic solvents are tetrahydrofuran anda cetonitrile. [122,123] For example, Xu et al reported CsPbBr 3 perovskite quantum dot (QD)-modified porous graphitic carbon nitride (g-C 3 N 4 )w ith excellent photocatalytic CO 2 conversion performance in acetonitrile, [122] yieldingv ariousp roducts,i ncluding CO, methane, and alcohols. However,o rganic solvents contain al arge number of different carbon sources; this makes it very difficult to determine if the obtained carbon results from the organic solvento rC O 2 .…”
Section: Liquid-phase Reactionmentioning
confidence: 99%